2000
DOI: 10.1177/15910199000060s125
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Unstable Plaques in Patients with Carotid Stenosis Using B-Mode Ultrasonography

Abstract: Distal embolism is a detrimental complication of stent placement for the carotid artery stenosis. To evaluate usefulness of B-mode ultrasonography (US) for the detection of unstable plaques in patients with carotid artery stenosis, we examined US in 46 arteries of 35 patients with carotid stenosis of >30%. The echogenicity of 46 carotid plaques was hyperechoic in 20 plaques, hypoechoic in 15, and mixed-echoic in 11. The echogenicity of carotid plaques was correlated with severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
(2 reference statements)
0
11
0
1
Order By: Relevance
“…Some studies have also shown that CYP450 plasma metabolite levels are associated with IS risk 17) , but few studies have focused on subclinical atherosclerosis. Certain carotid plaque phenotypes such as plaque instability may be important markers of vulnerable plaques susceptible to rupture, leading to stroke 21) . To our knowledge, our study is the first to investigate the association between the genetic variations of genes related to the CYP pathway and possible markers of vulnerable plaque or the effect of these genetic variants on CYP450 plasma echolucent plaques, indicating that these SNPs may be potential markers for plaque instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have also shown that CYP450 plasma metabolite levels are associated with IS risk 17) , but few studies have focused on subclinical atherosclerosis. Certain carotid plaque phenotypes such as plaque instability may be important markers of vulnerable plaques susceptible to rupture, leading to stroke 21) . To our knowledge, our study is the first to investigate the association between the genetic variations of genes related to the CYP pathway and possible markers of vulnerable plaque or the effect of these genetic variants on CYP450 plasma echolucent plaques, indicating that these SNPs may be potential markers for plaque instability.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral internal and common carotid arteries, as well as bifurcations, were examined for atherosclerotic plaque presence and was defined as an endoluminal protrusion of at least 1.5 mm or a focal thickening 50% of the intima-media thickness relative to the adjacent wall segment 11,21) . Thereafter, patients were divided into two groups: carotid plaque and noncarotid plaque groups.…”
Section: Carotid Ultrasonographymentioning
confidence: 99%
“…Carotid plaque was defined as an endoluminal protrusion of at least 1.5 mm or a focal thickening >50% of the intima-media thickness relative to the adjacent wall segment [7,25]. According to the results, the patients were divided into two groups: carotid plaque and non-carotid plaque groups.…”
Section: Methodsmentioning
confidence: 99%
“…The visualizable portions of the deep femoral artery and the superficial femoral artery were also assessed bilaterally. Endoluminal protrusions of ≥1.5 mm or a focal thickening >50% of the intima‐media thickness relative to the adjacent wall segment were considered plaques . In case of a plaque, we measured the plaque‐free arterial wall adjacent to the plaque.…”
Section: Methodsmentioning
confidence: 99%